RELATIONSHIP BETWEEN THE EXPOSURE OF MALARIA IN AN ENDEMIC ZONE AND ITS ASSOCIATION WITH CANCER INCIDENCE. : • Correlation between malaria and cancer in South American. - Martinez Marignac, Verónica; Mondragon, Leonel F.; Richard, Silvina (Jour Med Resh and Health Sci, 2024)
An inverse association between malaria infection and risk of cancer has been established worldwide, however nutritional, economical incomes, social parameters bias and cancer risk increased by year related to life style and other factors have not been studied in an endemic malaria region such as those in South America. The present analysis examines the association by malaria and cancer and neoplasm incidence, restricting analyses to studies performed by the Institute for Health Metrics and Evaluation (IHME) where data for South America for endemic countries (Suriname, Guyana, Ecuador, Peru, Venezuela, Colombia, Brazil, Bolivia) and non malaria endemic countries were available (Argentina, Paraguay). Uruguay and Chile were included as outliers per more than 10 years with no reported cases of Malaria. The authors reviewed available databases through 30 years, examining both sexes, people of 25 year of age and olders, and analyzed the association between malaria, year of incidence, nutrition and risk of having different types of cancers and neoplasm as they were defined by Global Health Data Exchange (GHDx) and IHME. An inverse association between malaria total cancer and a strong negative correlation with neoplasm was found in both sexes. This study confirms previous studies reporting an inverse association between malaria and cancer and provides quantitative estimates of the inverse association in South American countries. We suggest that two malaria non-endemic countries (Chile and Uruguay) have an elevated risk level of cancer incidence. We discuss possible mechanism of malaria infection as an antagonist to cancer or neoplasm development.